2011
DOI: 10.1007/s10592-011-0221-1
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of orchid bees (Euglossini) in anthropogenically altered landscapes

Abstract: Habitat degradation and fragmentation are widespread phenomena in tropical regions. Negative effects on the biota are numerous, ranging from interruption of gene flow among populations, to the loss of genetic diversity within populations, to a decline in species richness over time. Orchid bees (Hymenoptera: Apidae: Euglossini) are of major conservation interest due to their function as pollinators of numerous orchid species and other tropical plants. Here, we used microsatellite markers to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 80 publications
7
49
1
2
Order By: Relevance
“…championi are consistent with previous population genetic data on bees in the genus Euglossa. Zimmermann et al (2011) found low differentiation for eight species of Euglossa between sites separated by over 130 km of agricultural land, a much larger area than our study, in which the furthest forest fragments were 14 km apart. This study did not investigate levels of differentiation for any species in the genus Eulaema, a genus in which bees tend to be much larger.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…championi are consistent with previous population genetic data on bees in the genus Euglossa. Zimmermann et al (2011) found low differentiation for eight species of Euglossa between sites separated by over 130 km of agricultural land, a much larger area than our study, in which the furthest forest fragments were 14 km apart. This study did not investigate levels of differentiation for any species in the genus Eulaema, a genus in which bees tend to be much larger.…”
Section: Discussioncontrasting
confidence: 82%
“…A recent population genetic study of orchid bees in Mexico sought to tease apart the influences of habitat fragmentation and distance on genetic diversity and gene flow (Zimmermann et al 2011). These authors found low levels of genetic differentiation between sites separated by 130 km of agricultural land, and no difference in levels of differentiation between sites separated by forest or by agricultural land.…”
Section: Introductionmentioning
confidence: 99%
“…Considering our results, the pattern of isolation by distance exhibited by E. iopoecila also suggests that this orchid bee species shows limited dispersal ability when compared with other euglossine species. Despite this, the estimates of F ST and D est for E. iopoecila revealed by microsatellite markers did not differ conspicuously from those reported for populations of other euglossine species (Zimmermann et al 2011;Freiria et al 2012;Rocha-Filho et al 2013;Boff et al 2014;Suni et al 2014). These authors also used microsatellite markers to assess the population structure of different euglossine species and detected either a lack of genetic differentiation in the populations or levels of differentiation ranging from low to moderate.…”
Section: Pairs Of Populationsmentioning
confidence: 83%
“…Only Zimmermann et al (2011) and Suni and Brosi (2011), in their respective studies of Euglossa dilemma populations in Mexico and E. bombiformis in Costa Rica, detected a significant positive correlation between genetic distance and geographical distance for these species. Based on their findings, Suni and Brosi (2011) suggest that the mobility of orchid bees differs significantly among species.…”
Section: Pairs Of Populationsmentioning
confidence: 88%
See 1 more Smart Citation